KESANTUNAN BERBAHASA GENERASI ALPHA DALAM RUANG DIGITAL SEBUAH TINJAUAN SOSIOPRAGMATIK - Fitri, Elsa; Saleh, Muhammad (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2025)
AbstractThis study, "Reconstructing Digital Politeness in Generation Alpha," aims to describe the shifting meanings and practices of politeness in digital communication. The method used is descriptive qualitative, with data collection techniques including observation of digital interactions, conversation analysis, and in-depth interviews. The results show that Generation Alpha reconstructs politeness norms through multimodal expressions, such as the use of emojis, the normalization of teasing as a sign of closeness, and the assessment of politeness based on intention, not verbal form. Digital politeness is contextual, rapid, and platform-dependent, with a shift from linguistic formality to the ability to maintain social relationships. The study's conclusions confirm that politeness in Generation Alpha has not disappeared, but has transformed to suit the flexible and egalitarian nature of the digital space.